MCHP (Monte Carlo + Human Phantom): Platform to facilitate teaching nuclear radiation physics. - Mehrdad Shahmohammadi Beni (Public Library of Science (PLoS), 2021)
Some concepts in nuclear radiation physics are abstract and intellectually demanding. In the present paper, an "MCHP platform" (MCHP was an acronym for Monte Carlo simulations + Human Phantoms) was proposed to provide assistance to the students through visualization. The platform involved Monte Carlo simulations of interactions between ionizing radiations and the Oak Ridge National Laboratory (ORNL) adult male human phantom. As an example to demonstrate the benefits of the proposed MCHP platform, the present paper investigated the variation of the absorbed photon dose per photon from a 137Cs source in three selected organs, namely, brain, spine and thyroid of an adult male for concrete and lead shields with varying thicknesses. The results were interesting but not readily comprehensible without direct visualization. Graphical visualization snapshots as well as video clips of real time interactions between the photons and the human phantom were presented for the involved cases, and the results were explained with the help of such snapshots and video clips. It is envisaged that, if the platform is found useful and effective by the readers, the readers can also propose examples to be gradually added onto this platform in future, with the ultimate goal of enhancing students' understanding and learning the concepts in an undergraduate nuclear radiation physics course or a related course.